Character Education Analysis on the 4th Grade Elementary School’s 2013 Curriculum Instructional Materials in Legend Text - Widyani, Diah; Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research motivated by moral crises in the midst of Indonesian society. This research aim to analyze legend text on the 4th grade elementary school’s 2013 curriculum instructional materials in character education perspective. Five main values ​​of character education are religious, nationalist, independent, mutual cooperation, and integrity. The method used in this research was content analysis and the objects of this research were legend texts on the 4th grade elementary school’s student books on 2nd semester 2013 curriculum published by The Ministry of Education and Culture 2017 revised edition. Based on data analysis legend text on the 4th grade elementary school’s 2013 curriculum instructional materials contains five main values ​​of character education that reflected in the nine texts but does not fit entirely in one text. Five main values are religious, nationalist, independent, mutual cooperation, and integrity. Religious spread over three texts, nationalist spread over two text, independent spread over seven texts, mutual cooperation spread over nine texts, and integrity spread over seven texts.